2023
DOI: 10.1039/d2cs00928e
|View full text |Cite
|
Sign up to set email alerts
|

Smart probes for optical imaging of T cells and screening of anti-cancer immunotherapies

Abstract: T cells are an essential component of the immune system and display multiple biological functions. Smart probes range from small fluorophores to nanoconstructs, and can target metabolic and enzymatic biomarkers as well as cell-surface receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…These probes, therefore, can be used as realtime in vivo imaging agents. [82] Targeting metabolism-associated enzymes found in the tumor immune landscape such as those involved in nucleoside salvage pathway [83] and kynurenine pathway [84] has shown encouraging results for predicting immunotherapy response. Examples of small molecule metabolism-targeting probes include 18 F-FAC [85][86] and 18 F-CFA [87] (Figure 5A), radiolabeled substrates of deoxycytidine kinase (dCK) which is the rate-limiting enzyme in the nucleoside salvage pathway proliferating CD8 + T cells utilize for DNA synthesis [88] and 1-L-[ 18 F]-FETrp [89] (Figure 5B), a PET tracer developed to monitor indoleamine 2,3-dioxygenase (IDO)-mediated tryptophan metabolism that contributes to the immunosuppressive TME associated with poor clinical outcomes.…”
Section: Substrate and Activity-based Imaging Probesmentioning
confidence: 99%
“…These probes, therefore, can be used as realtime in vivo imaging agents. [82] Targeting metabolism-associated enzymes found in the tumor immune landscape such as those involved in nucleoside salvage pathway [83] and kynurenine pathway [84] has shown encouraging results for predicting immunotherapy response. Examples of small molecule metabolism-targeting probes include 18 F-FAC [85][86] and 18 F-CFA [87] (Figure 5A), radiolabeled substrates of deoxycytidine kinase (dCK) which is the rate-limiting enzyme in the nucleoside salvage pathway proliferating CD8 + T cells utilize for DNA synthesis [88] and 1-L-[ 18 F]-FETrp [89] (Figure 5B), a PET tracer developed to monitor indoleamine 2,3-dioxygenase (IDO)-mediated tryptophan metabolism that contributes to the immunosuppressive TME associated with poor clinical outcomes.…”
Section: Substrate and Activity-based Imaging Probesmentioning
confidence: 99%
“…9 Among various emerging strategies, fluorescence imaging has revolutionized the analysis of biological systems due to its advantages in temporal and spatial sampling, response rate, and high sensitivity, as well as non-radioactive characteristics. 10–13 Fluorescence imaging can be categorized into non-targeted and targeted fluorescence imaging to visualize and study different molecules or structures in biological samples. 14 Non-targeted fluorescent probes typically do not possess high specificity for a particular target biological molecule, and they may interact with multiple molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The tandem-locked optical probes have been developed for real-time tracking and noninvasive interpretation of the profiles, distribution, and functions of immune cells in tumors during cancer immunotherapy. It has been revealed that the immunotherapy efficacy varies with the infiltration of different immune cells, and detection of tumor-infiltrated immune cells could be applied for prognostic stratification and targeted therapy. , Mast cells, a prominent subset of tissue-resident immune cells, play a crucial role in allergic and other inflammatory diseases . However, their functions in modulation of the tumor immune microenvironment have been less understood.…”
Section: Introductionmentioning
confidence: 99%